High-strength high-silicon aluminum alloy and manufacturing method thereof
Through the secondary refining of argon + refining agent and nano alloy refining and aluminum strontium metamorphism treatment, the problem of primary crystal silicon and eutectic silicon size control in aluminum-silicon alloys is solved, and high-strength and high wear resistance is achieved, with excellent tensile strength and grain size.
Patent Information
- Application Number
- CN202411615294.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-18
AI Technical Summary
The existing aluminum-silicon alloys are insufficient in the application of high strength and wear resistance requirements such as automotive engines, especially in the control of size and form of primary and eutectic silicon, which leads to the failure of the comprehensive performance of the material to reach an excellent level.
The melt is refined by argon + refining agent and nano alloy refining, and the aluminum alloy solution is purified and grain refined by aluminum strontium metamorphism treatment to control the size of primary crystal silicon and eutectic silicon in high-silicon aluminum alloys.
A high-silicon aluminum alloy with high strength and wear resistance has a tensile strength of up to 440Mpa, the average size of primary crystal silicon remains below 40μm, and the average size of eutectic silicon is below 20μm, which significantly improves the overall performance of the material.
Smart Images

Figure CN119640103A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-strength and high-silicon aluminum alloy and a manufacturing method thereof, belonging to the technical field of aluminum alloy material production. Background Art
[0002] In the field of automobile manufacturing, there is an urgent demand for higher speed and higher power for engines. Traditional hypoeutectic and eutectic aluminum-silicon alloys can no longer meet the requirements for material strength and wear resistance such as engine pistons, transmission housings and transmission devices. The 4032 alloy is currently widely used in the market. As the requirements of the end-user continue to increase, various manufacturers are currently developing higher-strength aluminum alloy materials. Some manufacturers have begun to develop engine pistons and compressor dynamic and static plates in the direction of high-strength and high-silicon aluminum alloys. The alloy composition and internal structure of the alloy in high-strength aluminum alloys are the key to affecting the performance of high-silicon aluminum alloys. At present, the main key technology restricting the industrialization of hypereutectic aluminum-silicon alloys is the size and morphology control of primary silicon and eutectic silicon in the alloy. It is well known that when the average size of primary silicon in hypereutectic aluminum-silicon alloys is kept below 40μm, the average size of eutectic silicon is below 20μm, and the morphology of eutectic silicon is nearly spherical, hypereutectic aluminum-silicon alloys can have excellent comprehensive properties such as excellent mechanics, wear resistance and good dimensional stability. The current technology of using modifiers such as aluminum-phosphorus master alloys encounters great resistance during the industrialization process, making it difficult to achieve technology transfer and replication. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a high-strength and high-silicon aluminum alloy, which is manufactured according to the following weight percentages: 9.0% to 11.0% silicon, 2.5% to 3.5% copper, 0.3% to 0.7% magnesium, ≤0.3% manganese, ≤0.25% iron, ≤0.4% zinc, ≤0.2% titanium, and the remainder is aluminum and unavoidable impurity elements.
[0004] Preferably, the inevitable impurity elements are less than 0.15% in total, and the inevitable impurity elements include: Cr and Ni.
[0005] Preferably, the method for manufacturing a high-strength and high-silicon aluminum alloy comprises the following steps:
[0006] 1) Melting aluminum alloy according to mass ratio: weigh pure aluminum ingot, cathode copper, pure magnesium ingot, pure silicon particles, and aluminum manganese, aluminum iron, aluminum zinc and aluminum titanium master alloy according to the above mass percentage, set the melting furnace temperature to 900°C-1000°C, charge the pure aluminum ingot, pure silicon particles, cathode copper, and aluminum manganese, aluminum iron, aluminum zinc and aluminum titanium master alloy into the furnace, and after all are melted, control the furnace temperature between 720°C and 780°C, and stir at the same time, stirring for a total of 3 times, each stirring time is 15min, and the stirring interval is 30min, wherein the slag is skimmed after the first stirring, and the slag on the surface of the melt needs to be skimmed off, the melt temperature is raised to 730-750°C, and then the pure magnesium ingot and the metal additive are added, and then the remaining two stirrings are performed;
[0007] 2) Refining and heating: After the melt temperature obtained in step 1) reaches 760-780° C., secondary refining is performed, and after the two refinings, the surface scum is scraped off;
[0008] 3) Modification treatment: the melt obtained in step 2) is kept warm for 3 hours at a temperature of 760-770°C, stirred for 2 minutes after the end of the insulation process, and after the melt temperature reaches 750°C-765°C, an aluminum strontium modifier is added to perform a modification treatment on the melt;
[0009] 4) Casting: The metamorphosed melt obtained in step 3) is allowed to stand, and when the melt temperature stabilizes to 760°C, the melt is added to a casting plate for casting, and an ingot with a diameter of 355 is cast. During the casting process, AL-5Ti-1B refiner is added online, and the amount of aluminum titanium boron wire added is 3kg / ton. Argon gas is used for online degassing, and the online degassing rotor speed is set at 300±10rpm, and the argon gas flow rate is 3.0±0.3m 3 / h, 1 kg of aluminum strontium modifier is added to each partition 30 minutes before casting, and 30PPI+50PPI filter plates are used for online double-stage filtration. After the casting process is completed, a new type of high-silicon aluminum alloy casting rod is obtained;
[0010] 5) Homogenization: Metal temperature: 480±3℃, keep warm for 8 hours, air cool after leaving the furnace;
[0011] 6) Inspection: Low magnification: no slag inclusions, pores and compound aggregation were found, grain size ≤ level 1, looseness ≤ level 1; High magnification: primary silicon size <40μm, eutectic silicon size <20um;
[0012] 7) After the ingot is homogenized, it is extruded into rods in an extruder. The ingot heating temperature is 380-400℃, the discharge speed is 3-4m / min, and it is air-cooled online. Samples are taken for simulated T6 heat treatment. The quenching temperature is 500±3℃ for 90 minutes, and the aging temperature is 165±5℃ for 8 hours to verify the T6 related properties.
[0013] 8) Extrusion test: Low magnification: No cracks, shrinkage tails, pores and foreign inclusions were found in the low magnification sample, and the coarse grain ring was ≤1mm; High magnification: the size of primary silicon was <40μm, and the size of eutectic silicon was <20um.
[0014] Preferably, the metal additive in step 1) is a copper agent.
[0015] Preferably, the first refining in step 2) uses argon gas + refining agent refining, the refining agent is sodium-free granular refining agent MK4844B, the refining agent usage is 2 kg / ton, and the refining time is 15 minutes.
[0016] Preferably, in step 2), the second refining is performed by using nano alloy refining, firstly adding 2 kg / ton of nano alloy and stirring for 5 minutes before refining, and the refining time is 20 minutes.
[0017] Preferably, the amount of the modifier in step 3) is 2.25 kg / ton of aluminum strontium modifier, the number of stirring times is 1 time, the stirring time is 10 minutes, and the mixture is allowed to stand for 10 minutes after stirring.
[0018] Preferably, the modifier in step 3) is added using a special tool, and blowing refining in the furnace is strictly prohibited during and after the modification process, and the time interval from the start of refining to the start of casting is not allowed to exceed 90 minutes.
[0019] Preferably, in step 4), the amount of aluminum-titanium-boron wire added is 3 kg / ton, water is used for cooling during the casting process, the opening degree of the cooling water valve is ≥60%, and the casting speed is 48 mm / min to 52 mm / min.
[0020] The present invention provides a high-strength and high-silicon aluminum alloy and a manufacturing method thereof, wherein the melt is subjected to secondary refining by argon gas + refining agent refining and nano alloy refining, and aluminum strontium is used for modification to purify the aluminum alloy melt and refine the grains, and the size of primary silicon and eutectic silicon in the high-silicon aluminum alloy is controlled to achieve the requirements of high strength and high wear resistance of the material. Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:
[0021] 1. High strength, tensile strength can reach over 440Mpa.
[0022] 2. The matrix itself has better wear resistance than conventional 4032 aluminum alloy.
[0023] 3. Through secondary refining and aluminum-strontium modification, the average size of primary silicon is controlled to be below 40μm, and the average size of eutectic silicon is controlled to be below 20μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Image of primary silicon ingot.
[0025] Figure 2High magnification image of extruded rod. DETAILED DESCRIPTION
[0026] The present invention is described in detail below in conjunction with the accompanying drawings.
[0027] Example 1
[0028] A high-strength and high-silicon aluminum alloy is manufactured according to the following weight percentages: 9.0% silicon, 2.5% copper, 0.3% magnesium, 0.1% manganese, 0.15% iron, 0.2% zinc, 0.1% titanium, and the remainder is aluminum and inevitable impurity elements, the total amount of the inevitable impurity elements is less than 0.15%, and the inevitable impurity elements include: Cr, Ni.
[0029] The method for manufacturing a high-strength and high-silicon aluminum alloy comprises the following steps:
[0030] 1) Melting aluminum alloy according to mass ratio: weigh pure aluminum ingot, cathode copper, pure magnesium ingot, pure silicon particles, and aluminum-manganese, aluminum-iron, aluminum-zinc and aluminum-titanium master alloys according to the above-mentioned mass percentage, set the smelting furnace temperature to 900°C, charge the pure aluminum ingot, pure silicon particles, cathode copper, and aluminum-manganese, aluminum-iron, aluminum-zinc and aluminum-titanium master alloys into the furnace, and after all are melted, control the furnace temperature between 720°C and stir at the same time, stir 3 times in total, each stirring time is 15min, and the stirring interval is 30min. After the first stirring, slag is skimmed, and the slag on the surface of the melt needs to be skimmed off, the melt temperature is raised to 730°C, and then the pure magnesium ingot and the metal additive copper agent are added, and then the remaining two stirrings are performed;
[0031] 2) Refining and heating: After the melt temperature obtained in step 1) reaches 760°C, secondary refining is performed:
[0032] The first refining uses argon gas + sodium-free particle refining agent MK4844B, the refining agent usage is 2kg / ton, and the refining time is 15 minutes; the second refining uses nano alloy refining, first add 2kg / ton of nano alloy and stir for 5 minutes before refining, and the refining time is 20 minutes; after two refinings, scrape off the surface scum;
[0033] 3) Modification treatment: The melt obtained in step 2) is kept warm for 3 hours at a temperature of 760°C. After the insulation process is completed, it is stirred for 2 minutes. After the melt temperature reaches 750°C, an aluminum strontium modifier is added to modify the melt. The amount of modifier is 2.25 kg / ton of aluminum strontium modifier. The number of stirring times is 1 time. The stirring time is 10 minutes. After stirring, the melt is allowed to stand for 10 minutes. The modifier is added using a special tool. Blowing refining in the furnace is strictly prohibited during and after the modification process. The time interval from the start of refining to the start of casting is not allowed to exceed 90 minutes.
[0034] 4) Casting: The metamorphosed melt obtained in step 3) is allowed to stand, and when the melt temperature stabilizes to 760°C, the melt is added to a casting plate for casting, and an ingot with a diameter of 355 is cast. During the casting process, AL-5Ti-1B refiner is added online, and the amount of aluminum titanium boron wire added is 3kg / ton. Argon gas is used for online degassing, and the online degassing rotor speed is set at 300±10rpm, and the argon gas flow rate is 3.0±0.3m 3 / h, 1 kg of aluminum strontium modifier is added to each partition 30 minutes before casting, 30PPI+50PPI filter plates are used for online double-stage filtration, water is used for cooling during the casting process, the cooling water valve opening is 60%, the casting speed is 48mm / min, and a new type of high-silicon aluminum alloy casting rod is obtained after the casting process is completed;
[0035] 5) Homogenization: Metal temperature: 480±3℃, keep warm for 8 hours, air cool after leaving the furnace;
[0036] 6) Inspection: Low magnification: No slag inclusions, pores and compound aggregation were found, grain size ≤ Grade 1, looseness ≤ Grade 1; High magnification: primary silicon size <40μm, eutectic silicon size <20um, ingot primary silicon image (no primary silicon was found) Figure 1 As shown;
[0037] 7) After the ingot is homogenized, it is extruded into rods in an extruder. The ingot heating temperature is 380°C, the discharge speed is 3m / min, and it is air-cooled online. Samples are taken for simulated T6 heat treatment. The quenching temperature is 500±3°C for 90 minutes and the aging temperature is 165±5°C for 8 hours to verify the T6 related properties.
[0038] 8) Extrusion test: Low magnification: No cracks, shrinkage tails, pores and foreign inclusions were found in the low magnification sample, and the coarse grain ring was ≤1mm; High magnification: The size of primary silicon was <40μm, the size of eutectic silicon was <20um, and the high magnification image of the extruded rod (no primary silicon was found, and the size of eutectic silicon was <20um) was as follows: Figure 2 shown.
[0039] Example 2
[0040] A high-strength and high-silicon aluminum alloy is manufactured according to the following weight percentages: 9.5% silicon, 3.0% copper, 0.4% magnesium, 0.2% manganese, 0.18% iron, 0.3% zinc, 0.15% titanium, and the remainder is aluminum and inevitable impurity elements, the total amount of the inevitable impurity elements is less than 0.15%, and the inevitable impurity elements include: Cr, Ni.
[0041] The method for manufacturing a high-strength and high-silicon aluminum alloy comprises the following steps:
[0042] 1) Melting aluminum alloy according to mass ratio: weigh pure aluminum ingot, cathode copper, pure magnesium ingot, pure silicon particles, and aluminum-manganese, aluminum-iron, aluminum-zinc and aluminum-titanium master alloys according to the above-mentioned mass percentage, set the melting furnace temperature to 950°C, charge the pure aluminum ingot, pure silicon particles, cathode copper, and aluminum-manganese, aluminum-iron, aluminum-zinc and aluminum-titanium master alloys into the furnace, and after all are melted, control the furnace temperature between 740°C and stir at the same time, stir 3 times in total, each stirring time is 15min, and the stirring interval is 30min, wherein the slag is skimmed after the first stirring, and the slag on the surface of the melt needs to be skimmed off, the melt temperature is raised to 735°C, and then the pure magnesium ingot and the metal additive copper agent are added, and then the remaining two stirrings are performed;
[0043] 2) Refining and heating: After the melt temperature obtained in step 1) reaches 765°C, secondary refining is performed:
[0044] The first refining uses argon gas + sodium-free particle refining agent MK4844B, the refining agent usage is 2kg / ton, and the refining time is 15 minutes; the second refining uses nano alloy refining, first add 2kg / ton of nano alloy and stir for 5 minutes before refining, and the refining time is 20 minutes; after two refinings, scrape off the surface scum;
[0045] 3) Modification treatment: The melt obtained in step 2) is kept warm for 3 hours at a temperature of 760°C. After the insulation process is completed, it is stirred for 2 minutes. After the melt temperature reaches 755°C, an aluminum strontium modifier is added to modify the melt. The amount of modifier is 2.25 kg / ton of aluminum strontium modifier, the number of stirring times is 1 time, the stirring time is 10 minutes, and the melt is allowed to stand for 10 minutes after stirring. The modifier is added using a special tool. Blowing refining in the furnace is strictly prohibited during and after the modification process. The time interval from the start of refining to the start of casting is not allowed to exceed 90 minutes.
[0046] 4) Casting: The metamorphosed melt obtained in step 3) is allowed to stand, and when the melt temperature stabilizes to 760°C, the melt is added to a casting plate for casting, and an ingot with a diameter of 355 is cast. During the casting process, AL-5Ti-1B refiner is added online, and the amount of aluminum titanium boron wire added is 3kg / ton. Argon gas is used for online degassing, and the online degassing rotor speed is set at 300±10rpm, and the argon gas flow rate is 3.0±0.3m 3 / h, 1 kg of aluminum strontium modifier is added to each partition 30 minutes before casting, 30PPI+50PPI filter plates are used for online double-stage filtration, water is used for cooling during the casting process, the cooling water valve opening is 65%, the casting speed is 49mm / min, and a new type of high-silicon aluminum alloy casting rod is obtained after the casting process is completed;
[0047] 5) Homogenization: Metal temperature: 480±3℃, keep warm for 8 hours, air cool after leaving the furnace;
[0048] 6) Inspection: Low magnification: No slag inclusions, pores and compound aggregation were found, grain size ≤ Grade 1, looseness ≤ Grade 1; High magnification: primary silicon size <40μm, eutectic silicon size <20um, ingot primary silicon image (no primary silicon was found) Figure 1 As shown;
[0049] 7) After the ingot is homogenized, it is extruded into rods in an extruder. The ingot heating temperature is 385°C, the discharge speed is 3.6m / min, and it is air-cooled online. Samples are taken for simulated T6 heat treatment. The quenching temperature is 500±3°C for 90 minutes and the aging temperature is 165±5°C for 8 hours to verify the T6 related properties.
[0050] 8) Extrusion test: Low magnification: No cracks, shrinkage tails, pores and foreign inclusions were found in the low magnification sample, and the coarse grain ring was ≤1mm; High magnification: The size of primary silicon was <40μm, the size of eutectic silicon was <20um, and the high magnification image of the extruded rod (no primary silicon was found, and the size of eutectic silicon was <20um) was as follows: Figure 2 shown.
[0051] Example 3
[0052] A high-strength and high-silicon aluminum alloy is manufactured according to the following weight percentages: 10.0% silicon, 3.2% copper, 0.5% magnesium, 0.25% manganese, 0.20% iron, 0.35% zinc, 0.18% titanium, and the remainder is aluminum and inevitable impurity elements, the total amount of the inevitable impurity elements is less than 0.15%, and the inevitable impurity elements include: Cr, Ni.
[0053] The method for manufacturing a high-strength and high-silicon aluminum alloy comprises the following steps:
[0054] 1) Melting aluminum alloy according to mass ratio: weigh pure aluminum ingot, cathode copper, pure magnesium ingot, pure silicon particles, and aluminum-manganese, aluminum-iron, aluminum-zinc and aluminum-titanium master alloys according to the above-mentioned mass percentage, set the smelting furnace temperature to 980°C, charge the pure aluminum ingot, pure silicon particles, cathode copper, and aluminum-manganese, aluminum-iron, aluminum-zinc and aluminum-titanium master alloys into the furnace, and after all are melted, control the furnace temperature between 750°C and stir at the same time, stir 3 times in total, each stirring time is 15min, and the stirring interval is 30min, wherein the slag is skimmed after the first stirring, and the slag on the surface of the melt needs to be skimmed off, the melt temperature is raised to 740°C, and then the pure magnesium ingot and the metal additive copper agent are added, and then the remaining two stirrings are performed;
[0055] 2) Refining and heating: After the melt temperature obtained in step 1) reaches 770°C, secondary refining is performed:
[0056] The first refining uses argon gas + sodium-free particle refining agent MK4844B, the refining agent usage is 2kg / ton, and the refining time is 15 minutes; the second refining uses nano alloy refining, first add 2kg / ton of nano alloy and stir for 5 minutes before refining, and the refining time is 20 minutes; after two refinings, scrape off the surface scum;
[0057] 3) Modification treatment: The melt obtained in step 2) is kept warm for 3 hours at a temperature of 768°C. After the insulation process is completed, it is stirred for 2 minutes. After the melt temperature reaches 760°C, an aluminum strontium modifier is added to modify the melt. The amount of modifier is 2.25 kg / ton of aluminum strontium modifier, the number of stirring times is 1 time, the stirring time is 10 minutes, and the melt is allowed to stand for 10 minutes after stirring. The modifier is added using a special tool. Blowing refining in the furnace is strictly prohibited during and after the modification process. The time interval from the start of refining to the start of casting is not allowed to exceed 90 minutes.
[0058] 4) Casting: The metamorphosed melt obtained in step 3) is allowed to stand, and when the melt temperature stabilizes to 760°C, the melt is added to a casting plate for casting, and an ingot with a diameter of 355 is cast. During the casting process, AL-5Ti-1B refiner is added online, and the amount of aluminum titanium boron wire added is 3kg / ton. Argon gas is used for online degassing, and the online degassing rotor speed is set at 300±10rpm, and the argon gas flow rate is 3.0±0.3m 3 / h, 1 kg of aluminum strontium modifier is added to each partition 30 minutes before casting, 30PPI+50PPI filter plates are used for online double-stage filtration, water is used for cooling during the casting process, the cooling water valve opening is 68%, the casting speed is 50 mm / min, and a new type of high-silicon aluminum alloy casting rod is obtained after the casting process is completed;
[0059] 5) Homogenization: Metal temperature: 480±3℃, keep warm for 8 hours, air cool after leaving the furnace;
[0060] 6) Inspection: Low magnification: No slag inclusions, pores and compound aggregation were found, grain size ≤ Grade 1, looseness ≤ Grade 1; High magnification: primary silicon size <40μm, eutectic silicon size <20um, ingot primary silicon image (no primary silicon was found) Figure 1 As shown;
[0061] 7) After the ingot is homogenized, it is extruded into rods in an extruder. The ingot heating temperature is 380-400°C, the discharge speed is 3.8m / min, and it is air-cooled online. Samples are taken for simulated T6 heat treatment. The quenching temperature is 500±3°C for 90 minutes and the aging temperature is 165±5°C for 8 hours to verify the T6 related properties.
[0062] 8) Extrusion test: Low magnification: No cracks, shrinkage tails, pores and foreign inclusions were found in the low magnification sample, and the coarse grain ring was ≤1mm; High magnification: The size of primary silicon was <40μm, the size of eutectic silicon was <20um, and the high magnification image of the extruded rod (no primary silicon was found, and the size of eutectic silicon was <20um) was as follows: Figure 2 shown.
[0063] Example 4
[0064] A high-strength and high-silicon aluminum alloy is manufactured according to the following weight percentages: 11.0% silicon, 3.5% copper, 0.7% magnesium, 0.3% manganese, 0.25% iron, 0.4% zinc, 0.2% titanium, and the remainder is aluminum and inevitable impurity elements, the total amount of the inevitable impurity elements is less than 0.15%, and the inevitable impurity elements include: Cr, Ni.
[0065] The method for manufacturing a high-strength and high-silicon aluminum alloy comprises the following steps:
[0066] 1) Melting aluminum alloy according to mass ratio: weigh pure aluminum ingot, cathode copper, pure magnesium ingot, pure silicon particles, and aluminum-manganese, aluminum-iron, aluminum-zinc and aluminum-titanium master alloys according to the above-mentioned mass percentage, set the smelting furnace temperature to 1000°C, charge the pure aluminum ingot, pure silicon particles, cathode copper, and aluminum-manganese, aluminum-iron, aluminum-zinc and aluminum-titanium master alloys into the furnace, and after all are melted, control the furnace temperature between 780°C and stir at the same time, stir 3 times in total, each stirring time is 15min, and the stirring interval is 30min. After the first stirring, slag is skimmed, and the slag on the surface of the melt needs to be skimmed off, the melt temperature is raised to 750°C, and then the pure magnesium ingot and the metal additive copper agent are added, and then the remaining two stirrings are performed;
[0067] 2) Refining and heating: After the melt temperature obtained in step 1) reaches 780°C, secondary refining is performed:
[0068] The first refining uses argon gas + sodium-free particle refining agent MK4844B, the refining agent usage is 2kg / ton, and the refining time is 15 minutes; the second refining uses nano alloy refining, first add 2kg / ton of nano alloy and stir for 5 minutes before refining, and the refining time is 20 minutes; after two refinings, scrape off the surface scum;
[0069] 3) Modification treatment: The melt obtained in step 2) is kept warm for 3 hours at a temperature of 770°C. After the insulation process is completed, it is stirred for 2 minutes. After the melt temperature reaches 765°C, an aluminum strontium modifier is added to modify the melt. The amount of modifier is 2.25 kg / ton of aluminum strontium modifier, the number of stirring times is 1 time, the stirring time is 10 minutes, and the melt is allowed to stand for 10 minutes after stirring. The modifier is added using a special tool. Blowing refining in the furnace is strictly prohibited during and after the modification process. The time interval from the start of refining to the start of casting is not allowed to exceed 90 minutes.
[0070] 4) Casting: The metamorphosed melt obtained in step 3) is allowed to stand, and when the melt temperature stabilizes to 760°C, the melt is added to a casting plate for casting, and an ingot with a diameter of 355 is cast. During the casting process, AL-5Ti-1B refiner is added online, and the amount of aluminum titanium boron wire added is 3kg / ton. Argon gas is used for online degassing, and the online degassing rotor speed is set at 300±10rpm, and the argon gas flow rate is 3.0±0.3m 3 / h, 1 kg of aluminum strontium modifier is added to each partition 30 minutes before casting, 30PPI+50PPI filter plates are used for online double-stage filtration, water is used for cooling during the casting process, the cooling water valve opening is 70%, the casting speed is 52mm / min, and a new type of high-silicon aluminum alloy casting rod is obtained after the casting process is completed;
[0071] 5) Homogenization: Metal temperature: 480±3℃, keep warm for 8 hours, air cool after leaving the furnace;
[0072] 6) Inspection: Low magnification: No slag inclusions, pores and compound aggregation were found, grain size ≤ Grade 1, looseness ≤ Grade 1; High magnification: primary silicon size <40μm, eutectic silicon size <20um, ingot primary silicon image (no primary silicon was found) Figure 1 As shown;
[0073] 7) After the ingot is homogenized, it is extruded into rods in an extruder. The ingot heating temperature is 400°C, the discharge speed is 4m / min, and it is air-cooled online. Samples are taken for simulated T6 heat treatment. The quenching temperature is 500±3°C for 90 minutes and the aging temperature is 165±5°C for 8 hours to verify the T6 related properties.
[0074] 8) Extrusion test: Low magnification: No cracks, shrinkage tails, pores and foreign inclusions were found in the low magnification sample, and the coarse grain ring was ≤1mm; High magnification: The size of primary silicon was <40μm, the size of eutectic silicon was <20um, and the high magnification image of the extruded rod (no primary silicon was found, and the size of eutectic silicon was <20um) was as follows: Figure 2 shown.
[0075] Element:
[0076]
[0077] T6 mechanical properties:
[0078] Alloy state Tensile strength / Mpa Yield strength / Mpa Elongation / % AHS-7 / T6 442 373 7.78 AHS-7 / T6 451 382 9.33
[0079] The above-described embodiments only express the preferred embodiments of the present invention, and the description thereof is relatively specific and detailed, but the present invention is not limited to these embodiments. It should be noted that it is obvious to those skilled in the art. Without departing from the purpose of the present invention, any improvement made shall fall within the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A high-strength, high-silicon aluminum alloy, characterized in that: The aluminum alloy is manufactured according to the following weight percentages: 9.0% to 11.0% silicon, 2.5% to 3.5% copper, 0.3% to 0.7% magnesium, ≤0.3% manganese, ≤0.25% iron, ≤0.4% zinc, ≤0.2% titanium, and the remainder is aluminum and unavoidable impurity elements.
2. A high-strength, high-silicon aluminum alloy according to claim 1, characterized in that: The total amount of the inevitable impurity elements is less than 0.15%, and the inevitable impurity elements include: Cr and Ni.
3. The method for manufacturing a high-strength and high-silicon aluminum alloy according to claim 1, characterized in that: The following steps are involved: 1) Melting aluminum alloy according to mass ratio: weigh pure aluminum ingot, cathode copper, pure magnesium ingot, pure silicon particles, and aluminum manganese, aluminum iron, aluminum zinc and aluminum titanium master alloy according to the above mass percentage, set the melting furnace temperature to 900°C-1000°C, charge the pure aluminum ingot, pure silicon particles, cathode copper, and aluminum manganese, aluminum iron, aluminum zinc and aluminum titanium master alloy into the furnace, and after all are melted, control the furnace temperature between 720°C and 780°C, and stir at the same time, stirring for a total of 3 times, each stirring time is 15min, and the stirring interval is 30min, wherein the slag is skimmed after the first stirring, and the slag on the surface of the melt needs to be skimmed off, the melt temperature is raised to 730-750°C, and then the pure magnesium ingot and the metal additive are added, and then the remaining two stirrings are performed; 2) Refining and heating: After the melt temperature obtained in step 1) reaches 760-780° C., secondary refining is performed, and after the two refinings, the surface scum is scraped off; 3) Modification treatment: the melt obtained in step 2) is kept warm for 3 hours at a temperature of 760-770°C, stirred for 2 minutes after the end of the insulation process, and after the melt temperature reaches 750°C-765°C, an aluminum strontium modifier is added to perform a modification treatment on the melt; 4) Casting: The metamorphosed melt obtained in step 3) is allowed to stand, and when the melt temperature stabilizes to 760°C, the melt is added to a casting plate for casting, and an ingot with a diameter of 355 is cast. During the casting process, AL-5Ti-1B refiner is added online, and argon gas is used for online degassing. The online degassing rotor speed is set at 300±10rpm, and the argon gas flow rate is 3.0±0.3m 3 / h, 1 kg of aluminum strontium modifier is added to each partition 30 minutes before casting, and 30PPI+50PPI filter plates are used for online double-stage filtration. After the casting process is completed, a new type of high-silicon aluminum alloy casting rod is obtained; 5) Homogenization: Metal temperature: 480±3℃, keep warm for 8 hours, air cool after leaving the furnace; 6) Inspection: Low magnification: no slag inclusions, pores and compound aggregation were found, grain size ≤ level 1, looseness ≤ level 1; High magnification: primary silicon size <40μm, eutectic silicon size <20um; 7) After the ingot is homogenized, it is extruded into rods in an extruder. The ingot heating temperature is 380-400℃, the discharge speed is 3-4m / min, and it is air-cooled online. Samples are taken for simulated T6 heat treatment. The quenching temperature is 500±3℃ for 90 minutes, and the aging temperature is 165±5℃ for 8 hours to verify the T6 related properties. 8) Extrusion test: Low magnification: No cracks, shrinkage tails, pores and foreign inclusions were found in the low magnification sample, and the coarse grain ring was ≤1mm; High magnification: the size of primary silicon was <40μm, and the size of eutectic silicon was <20um.
4. The method for manufacturing a high-strength and high-silicon aluminum alloy according to claim 3, characterized in that: In step 1), the metal additive is a copper agent.
5. The method for manufacturing a high-strength and high-silicon aluminum alloy according to claim 3, characterized in that: In step 2), the first refining is performed using argon gas + refining agent, the refining agent is sodium-free granular refining agent MK4844B, the amount of refining agent used is 2 kg / ton, and the refining time is 15 minutes.
6. The method for manufacturing a high-strength and high-silicon aluminum alloy according to claim 3, characterized in that: In step 2), the second refining is performed by using nano alloy refining again. First, 2 kg / ton of nano alloy is added and stirred for 5 minutes before refining. The refining time is 20 minutes.
7. The method for manufacturing a high-strength and high-silicon aluminum alloy according to claim 3, characterized in that: The amount of modification in step 3): 2.25kg / ton aluminum strontium modifier, stirring times: 1 time, stirring time: 10 minutes, let stand for 10 minutes after stirring.
8. The method for manufacturing a high-strength and high-silicon aluminum alloy according to claim 3, characterized in that: The modifier in step 3) is added using a special tool. Blowing refining in the furnace is strictly prohibited during and after the modification process. The time interval from the start of refining to the start of casting is not allowed to exceed 90 minutes.
9. The method for manufacturing a high-strength and high-silicon aluminum alloy according to claim 3, characterized in that: In step 4), the amount of aluminum titanium boron wire added is 3 kg / ton, water is used for cooling during the casting process, the opening degree of the cooling water valve is ≥60%, and the casting speed is 48 mm / min to 52 mm / min.